An evaluation of distinct adeno-associated virus vector strategies for driving transgene expression in spinal inhibitory neurons of the rat - Laura Klinger; Anna S. M. Siegert; Raphael Holzinger; Lidia Trofimova; Sibel Ada; Ruth Drdla-Schutting (Frontiers in Neuroscience)
The spinal cord dorsal horn (DH) is essential for processing and transmitting nociceptive information. Its neuronal subpopulations exhibit significant heterogeneity in morphology and intrinsic properties, forming complex circuits that remain only partially understood. Under physiological and pathological conditions, inhibitory interneurons in the DH are of particular interest. These neurons modulate and refine pain-related signals entering the central nervous system. The ability to selectively target these inhibitory interneurons is key to investigating the underlying circuitry and mechanisms of pain processing, as well as to understand the specific role of inhibitory signaling within these processes. We employed a viral vector approach to deliver a fluorescent reporter protein specifically to inhibitory interneurons in the rat spinal cord. Using adeno-associated virus (AAV) vectors designed to express enhanced green fluorescent protein (EGFP) under the control of various promoters, we targeted distinct subtypes of spinal inhibitory interneurons. Through immunostaining, in situ hybridization, and confocal imaging, we evaluated the specificity and efficacy of these promoters. Our findings revealed that the promoter/vector combinations used did not achieve the desired specificity for targeting distinct interneuron populations in the DH. Despite these limitations, this work provides valuable insights into the potential and challenges of designing AAV-based approaches for selective neuronal targeting. These results emphasize the need for further refinement of promoter designs to achieve precise and reliable expression in specific spinal interneuron subtypes. Addressing these challenges will be crucial for advancing our understanding of spinal nociceptive circuits and developing targeted therapeutic approaches for pain syndromes.